Atrial sensing to augment ventricular tachycardia detection by the automatic implantable cardioverter defibrillator: a utility study. - Schuger CD; Jackson K; Steinman RT; Lehmann MH (Pacing & Clinical Electrophysiology, 1988)
The triggering of automatic implantable cardioverter defibrillator (AICD) discharges by supraventricular tachycardias, despite the presence of a probability density/unction algorithm, remains a limitation of an otherwise highly effective device. We systematically investigated the diagnostic utility which theoretically could derive form the addition of atrial sensing capability to the AICD in 25 patients with 30 inducible sustained monomorphic ventricular tachycardias (VTs) at clinically relevant rates ( 150 beats/min). Patients were included only if they were not taking medication capable of depressing ventriculoatrial (VA) conduction for at least 5 half-lives prior to electrophysiological testing. We tested the simple criterion for VT that ventricular cycle length (CL) be shorter than the atrial CL (not met in sinus or most other supraventricular tachycardias). Mean VT CL was 283 ± 47 ms (range 210 to 370). In 25 (83%) VTs, the VT criterion was consistently satisfied. Of the five cases in which the criterion was not met, 1:1 VA conduction during VT was present in four, three of which initially manifested 2:1 VA conduction lasting from 14 to 28 s and therefore would have transiently fulfilled the VT criterion. The remaining patient who failed to satisfy the VT criterion had ongoing atrial flutter during a relatively slower sustained VT, but this circumstance could be recognized because of the varying AV interval. The absence of 1:1 VA conduction at CLS < 400 ms during ventricular pacing accurately predicted the absence of 1:1 VA conduction during VT in 95% of patients. Overall, then, use of the simple VT criterion early after tachycardia onset - in tandem with AV interval tracking - would have correctly identified 29/30 (97%) VTs. We conclude that simple incorporation of atrial sensing capability into the AICD, with corresponding software modification, is likely to facilitate differentiation of VT from supraventricular tachycardia in the vast majority of patients.